If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16f = 15f + 2 Reorder the terms: 16f = 2 + 15f Solving 16f = 2 + 15f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-15f' to each side of the equation. 16f + -15f = 2 + 15f + -15f Combine like terms: 16f + -15f = 1f 1f = 2 + 15f + -15f Combine like terms: 15f + -15f = 0 1f = 2 + 0 1f = 2 Divide each side by '1'. f = 2 Simplifying f = 2
| -10x^2-65x-75=0 | | 10-3r+5+2r= | | h(t)=V*t-16*t^2 | | x-(x+17)=2(11-3x) | | 5=v/20 | | x+6=3-2 | | W-w=3 | | 5n=250 | | 7x+1=15x+3 | | 2(x+3)=6(3) | | f+g/2 | | 1/6+5/12x=5/6 | | -28+15-22z=33 | | (a-5)-3=12 | | 2/3(v-6)=1/3(v+6) | | -(6a+1)+2(3-a)=a | | 14.3-(-21.2)= | | 2(4x+2)=8x+4 | | 4(3+y)=-y+8 | | In=4 | | -15+-18= | | 0+(-10)= | | Y+5=5+y | | 18x^2+11x+15=0 | | 6n-10=22 | | Sinx=4 | | 4(3+y)=y+8 | | 17-5(3x+1)=10*10 | | 4p-2=35 | | X/4=17/2 | | -95-100= | | (95)-100= |